Advances in Fuzzy Decision Making Theory and Practice - Skalna, Iwona; Rębiasz, Bogdan; Gaweł, Bartłomiej; Basiura, Beata; Duda, Jerzy; Opiła, Janusz; Pełech-Pilichowski, Tomasz (Studies in Fuzziness and Soft Computing, 2015)
This book shows how common operation management methods and algorithms can be extended to deal with vague or imprecise information in decision-making problems. It describes how to combine decision trees, clustering, multi-attribute decision-making algorithms and Monte Carlo Simulation with the mathematical description of imprecise or vague information, and how to visualize such information. Moreover, it discusses a broad spectrum of real-life management problems including forecasting the apparent consumption of steel products, planning and scheduling of production processes, project portfolio selection and economic-risk estimation. It is a concise, yet comprehensive, reference source for researchers in decision-making and decision-makers in business organizations alike.